Role of preoperative and intraoperative factors in mediating infection complication following percutaneous nephrolithotomy - B. Lojanapiwat (2018)
Objective: To identify the pre- and intraoperative factors that affect the development of postoperative systemic inflammatory response syndrome (SIRS) following percutaneous nephrolithotomy (PCNL). Patients and Methods: A total of 200 patients were treated with PCNL, 56 of which developed postoperative SIRS (group I) and 144 did not (group II). For these 2 groups, the patient factor, operative factor, preoperative urine culture, pelvic urine culture, and stone culture were compared. Results: Average age, stone size, operative time, success rate, and number of tubeless PCNL were not significantly different between the 2 groups. However, preoperative urine culture, pelvic urine culture, and stone culture, respectively, were positive in 66.1, 46.4 and 48.2% of the patients in group I, but only 10.4, 3.5 and 3.5% for the corresponding specimens in group II. In addition, 5 patients in group I developed clinical septic shock, 4 of which were positive for all cultures and 1 positive only for stone culture. Conclusion: Infection following PCNL is common, but only a few cases progress to septic shock. Positive preoperative urine, intraoperative pelvic urine and stone cultures are important factors indicating the development of postoperative SIRS. Intraoperative cultures are important for decision-making about the treatment of postoperative infection complications. Copyright © 2011 S. Karger AG, Basel.